2021
DOI: 10.1021/acscatal.1c02995
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Coke-free Ni Catalyst Stabilized by 1–2 nm-Thick Multielement Oxide for Methane Dry Reforming

Abstract: Methane dry reforming, co-converting greenhouse gases CH 4 and CO 2 into chemically active syngas (H 2 /CO), affords a promising route for producing chemicals and fuels from carbon resources. Ni catalysts are the most active for this reaction but suffer from the dilemma of rapid deactivation caused by metal sintering at higher temperatures (>973 K) or coke accumulation at relatively lower temperatures (673−973 K). Here, we report a catalyst configurationNi particles (15 nm) confined by a 1−2 nm-thick multiele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Except for the core-shell encapsulation configuration, some studies also tried to coat some thin metal oxide layers to stabilize the Ni particles on support. [100,107] He et al coated the Si layer on Ni/Mg-Al hydrotalcite nanosheets, and a 1$2 nm thin layer was formed outside the Ni sites containing Si, Mg, and Al after H 2 reduction. [100] And Jin et al deposited the ZrO 2 film via atomic layer deposition (ALD) on the Ni/Al 2 O 3 catalyst.…”
Section: Encapsulation Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for the core-shell encapsulation configuration, some studies also tried to coat some thin metal oxide layers to stabilize the Ni particles on support. [100,107] He et al coated the Si layer on Ni/Mg-Al hydrotalcite nanosheets, and a 1$2 nm thin layer was formed outside the Ni sites containing Si, Mg, and Al after H 2 reduction. [100] And Jin et al deposited the ZrO 2 film via atomic layer deposition (ALD) on the Ni/Al 2 O 3 catalyst.…”
Section: Encapsulation Configurationmentioning
confidence: 99%
“…[100,107] He et al coated the Si layer on Ni/Mg-Al hydrotalcite nanosheets, and a 1$2 nm thin layer was formed outside the Ni sites containing Si, Mg, and Al after H 2 reduction. [100] And Jin et al deposited the ZrO 2 film via atomic layer deposition (ALD) on the Ni/Al 2 O 3 catalyst. [107] In these studies, with engineering-confined strategies, the catalyst showed improved coke resistance and less tendency of Ni sintering and migrating.…”
Section: Encapsulation Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, the unsaturated coordination sites, such as edge, corner, and vertex sites, with higher catalytic activity on the Ni particles are lost if the particle agglomeration happened, which in turn affects the catalytic activity . To overcome these drawbacks, several approaches have been explored as follows: (i) modification of active sites by adding the secondary metal to suppress the decomposition of CH 4 , , (ii) utilization of basic or redox supports to facilitate the activation of CO 2 to gasify the deposited carbon species, and (iii) construction of confinement structures to immobilize Ni nanoparticles (NPs) to protect the active species from agglomeration during the MDR process. …”
Section: Introductionmentioning
confidence: 99%
“…The stoichiometry syngas produced in MDR is suitable for preparing high value-added chemicals via Fischer–Tropsch synthesis, which is also crucial for mitigating greenhouse gas emissions. Considering the low cost and comparable activity with noble metals, Ni-based catalysts have become one of the most promising choices for MDR. However, coking and sintering of active metal causes the serious deactivation of Ni-based catalysts during the MDR process. Traditional strategies to solve these problems are controlling the Ni particle size via well-confined structured catalysts, utilizing basic supports to enrich the surface oxygen vacancies, and adding the secondary metals to increase the dispersion of Ni particles. Most of the strategies mentioned in the literature utilize metal oxides as the support of catalysts, which can promote the catalytic activity significantly. Nevertheless, the coking issue is still a formidable one to eliminate.…”
Section: Introductionmentioning
confidence: 99%